No Graduated Pressure Profile in Compression Stockings Still Reduces Muscle Fatigue - Miyamoto, N.; Kawakami, Y. (International Journal of Sports Medicine, 2015)
Most sporting compression stockings possess a graduated pressure profile. However, it remains unclear whether the graduated pressure profile is an essential feature for reducing the development of muscle fatigue. This study sought to examine the effect of the pressure profile of compression stockings on the degree of muscle fatigue of lower leg muscles induced by submaximal running exercise. 15 male subjects performed 30-min treadmill running in 1 control and 4 compression stocking conditions with the following profiles; 1) graduated low pressure, 2) graduated high pressure, 3) uniform pressure distribution, and 4) localized pressure just over the gastrocnemius muscle belly. Before and immediately after the exercise, T2-weighted magnetic resonance images of the right lower leg were obtained without testing garments. T2 values of the triceps surae and tibialis anterior were calculated from the images. T2 was significantly increased after the running in all conditions. The magnitude of T2 increase was significantly greater in the control than in other 3 conditions except for the one with graduated low pressure, whereas there were no significant differences among the latter 3 conditions. The findings suggest that a graduated pressure profile is not an essential feature of compression stockings for reducing the development of muscle fatigue during submaximal running exercise.
Keywords: compression garments; treadmill running; magnetic resonance imaging; triceps surae; tibialis anterior